SYNTHESISAND CHARACTERIZATION OFNATURALRUBBER-SILICACOMPOSITE - Indra Gunawan; Hildayati Hildayati; Sudirman Sudirman; Emil Budianto (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2011)
SYNTHESISAND CHARACTERIZATION OFNATURALRUBBER-SILICACOMPOSITE. The composite of natural rubber-silica have been developed with a combination of silica (SiO2)particles in irradiated natural rubber. This research was conducted with the aim to composite material with irradiated natural rubber as the matrix and silica particles as filler and to study the distribution of silica in the matrix as well as mechanical and physical properties. The results showed that the SiO2 particles homogenously distributed across the surface of natural rubber matrix as the cluster. The particles are arranged as a cluster by using 3-aminopropyltriethoxysilane (APTES) as a coupling agent. Tensile strength, tensile modulus and elongation at break of composite materials have increased as the addition of SiO2 on the composition of 9 to 12 percent weight in natural rubber. Additions of SiO2 composition in the matrix will also increase the hardness of the composite. Structural analysis were performed using FT-IR and SEM. Composite of natural rubber-SiO2 have a great potential to be applied as a natural rubber base materials mainly as protective products with higher performance.